2000
DOI: 10.1103/physreve.62.5518
|View full text |Cite
|
Sign up to set email alerts
|

Symbolic dynamics of event-related brain potentials

Abstract: We apply symbolic dynamics techniques such as word statistics and measures of complexity to nonstationary and noisy multivariate time series of electroencephalograms (EEG) in order to estimate event-related brain potentials (ERP). Their significance against surrogate data as well as between different experimental conditions is tested. These methods are validated by simulations using stochastic dynamical systems with time-dependent control parameters and compared with traditional ERP-analysis techniques. Contin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
67
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 69 publications
(69 citation statements)
references
References 52 publications
2
67
0
Order By: Relevance
“…The common overlap of their time ranges across trials yields again a measure of the intertrial coherence. However, these coarse-graining techniques were lacking a theoretical foundation that has recently been provided by beim Graben et al [6] (cf. [3,5,16]) in the framework of symbolic dynamics [18,23].…”
Section: Symbolic Resonance Analysismentioning
confidence: 99%
See 4 more Smart Citations
“…The common overlap of their time ranges across trials yields again a measure of the intertrial coherence. However, these coarse-graining techniques were lacking a theoretical foundation that has recently been provided by beim Graben et al [6] (cf. [3,5,16]) in the framework of symbolic dynamics [18,23].…”
Section: Symbolic Resonance Analysismentioning
confidence: 99%
“…2 After collecting all the sequences corresponding to one experimental condition in an ensemble, the number of b+Q or bÀQ symbols across all trials yields the polarity histogram [8]. beim Graben et al [6] have shown that these polarity histograms can be formally captured by probability measures of cylinder sets, which are subsets drawn from an ensemble of sequences having a common building block, which is called a word. beim Graben et al [6] have further argued that ERP components are characterized by large cylinder sets corresponding to a particular word.…”
Section: Symbolic Resonance Analysismentioning
confidence: 99%
See 3 more Smart Citations